Integrated bioinformatic approach of Balur therapy for breast cancer subtypes - Aristyani Sherry; Subagjo Saraswati; Rahayu Tintrim; Sumitro Sutiman B. (BIO Web of Conferences)
Balur is a topical complementary alternative medicine that can be applied to breast cancer. Balur eliminates free radicals and heavy metals which it found enhance in cancer patients compared with healthy persons. Balur uses materials that potentially can halt cancer progression and development such as aspirin, coffee, moringa, and tobacco. This study was to describe the complexity of Balur in the biological system of breast cancer subtypes such as luminal A, liminal B, and HER-2, which had been found in high numbers in Indonesia, with an integrative bioinformatic approach. Active compounds found from literature studies were collected and screened by skin permeability variables. For breast cancer subtypes, differential expressed gene (DEG) identification was used to explore the target of Balur compounds. The Cytoscape software was used to construct the network of Balur compounds and target proteins of breast cancer subtypes. Gene Ontology, pathway, docking, hub gene, and survival analysis were applied to investigate the detailed mechanism of Balur to breast cancer in each subtype. The results showed that Balur compounds targeted respectively 68, 86, and 84 genes of luminal A, luminal B, and HER-2. From these target genes, 7 Balur compounds had higher binding energy than chemotherapy compounds when they docked with hub genes from each subtype. In conclusion, this study explained the pharmacological mechanisms of Balur therapy, which has great potential as a complementary therapy for breast cancer subtypes.